Sociodemographic and socioeconomic differences in sleep duration and insomnia-related symptoms in Finnish adults - Lallukka Tea; Sares-Jäske Laura; Kronholm Erkki; Sääksjärvi Katri; Lundqvist Annamari; Partonen Timo; Rahkonen Ossi; Knekt Paul (BMC, 2012)
Abstract Background Poor sleep tends to be patterned by sociodemographic and socioeconomic factors. The aim of this study was to examine the associations of sociodemographic and socioeconomic factors with sleep duration and insomnia-related symptoms across life course. Methods We used cross-sectional Health 2000 Survey (2000-2001) among a total of 5,578 adult Finns, aged 30-79 years, representative of adult Finnish population. Data about sociodemographic and socioeconomic circumstances, insomnia-related symptoms over the previous month as well as average sleep duration were collected by questionnaires. Multinomial logistic regression models were adjusted first for gender and age, second for sociodemographic factors, third additionally for socioeconomic factors, and fourth for all covariates and self-perceived health simultaneously. Results On average 70% of Finnish adults slept 7-8 hours a day. Frequent insomnia-related symptoms were more prevalent among women (14%) than men (10%). Not being married, not having children, having low education, low income, being unemployed, and being a disability retiree were associated with frequent insomnia-related symptoms. Similar factors were associated with short and long sleep duration. However, childhood socioeconomic position was mostly unrelated to sleep in adulthood except parental education had some associations with short sleep duration. Conclusions Disadvantaged socioeconomic position in adulthood, in particular income and employment status, is associated with poorer sleep. When promoting optimal sleep duration and better sleep quality, families with low incomes, unemployed people, and disability retirees should be targeted.